Flow properties of ash and slag under co-gasification of coal and extract residue of direct coal liquefaction residue. (15th March 2020) - Cao, Xi; Peng, Baozi; Kong, Lingxue; Bai, Jin; Ge, Zefeng; Li, Huaizhu; Liu, Zhen; Feng, Ziyang; Bi, Dapeng; Bai, Zongqing; Szlęk, Andrzej; Li, Wen
Highlights: Extraction residue has strong crystallization tendency and unable gasify alone. The decreasing of quartz and anorthite content resulted in the AFTs decreased. The slag viscosity decreased due to the high content of calcium and iron. The slag showed a crystalline slag behavior as the extraction residue content increased to 25%. The best blended ratio should be 10–20% within the tapping temperature range of 1258–1575 °C. Abstract: Efficient utilization of the extraction residue (ER) of direct coal liquefaction residue is a bottle neck for the efficiency of direct coal liquefaction process. The co-gasification of the ER and coal is a promising way for large-scale utilization of ER. Flow properties of the feedstock including ash fusibility and slag viscosity are important parameters for the gasification process. To optimize co-gasification of the ER and coal, the ash fusibility and slag viscosity behavior of ER and coal under gasification conditions were studied. The results show that the ash fusion temperatures (AFTs) of the blending were lowered with the increasing blending ratio of ER due to the high content of calcium and iron in ER. The content of quartz and anorthite in the blended ashes decreased with the increasing ER blending ratio. The slag viscosities at high temperatures also decreased as the blending ratio of ER increased. The high content of calcium and iron in ER resulted in the decrease in the slag polymerization degree because of the break of Si-O structure and transformation from [AlO4 ] 5− to [AlO6 ] 9− . Besides, the slag presented the behavior of a crystalline slag when the ER blending ratio was increased up to 25% for the formation of anorthite during cooling. For the entrained flow gasification, the ER addition can effectively lower the operation temperature of the gasifiers, improve the gasification efficiency and avoid the slag tapping problems. The optimal ER addition should be in the range of 10–20%, and the corresponding tapping temperature was 1258–1575 °C.